Freeze-casting porous chitosan ureteral stents for improved drainage. (15th January 2019) - Yin, Kaiyang; Divakar, Prajan; Wegst, Ulrike G.K.
Graphical abstract: Abstract: As a new strategy for improved urinary drainage, in parallel to the potential for additional functions such as drug release and self-removal, highly porous chitosan stents are manufactured by radial, bi-directional freeze-casting. Inserting the porous stent in to a silicone tube to emulate its placement in the ureter shows that it is shape conforming and remains safely positioned in place, also during flow tests, including those performed in a peristaltic pump. Cyclic compression tests on fully-hydrated porous stents reveal high stent resilience and close to full elastic recovery upon unloading. The drainage performance of the chitosan stent is evaluated, using effective viscosity in addition to volumetric flow and flux; the porous stent's performance is compared to that of the straight portion of a commercial 8 Fr double-J stent which possesses, in its otherwise solid tube wall, regularly spaced holes along its length. Both the porous and the 8 Fr stent show higher effective viscosities, when tested in the silicone tube. The performance of the porous stent improves considerably more (47.5%) than that of the 8 Fr stent (30.6%) upon removal from the tube, illustrating the effectiveness of the radially aligned porosity for drainage. We conclude that the newly-developed porous chitosan ureteral stent merits further in vitro and in vivo assessment of its promise as an alternative and complement to currently available medical devices. Statement of Significance: No papers, to date, report on porous ureteral stents, which we propose as a new strategy for improved urinary drainage. The highly porous chitosan stents of our study are manufactured by radial, bi-directional freeze casting. Cyclic compression tests on fully-hydrated porous stents revealed high stent resilience and close to full recovery upon unloading. The drainage performance of the chitosan is evaluated, using effective viscosity in addition to volumetric flow and flux, and compared to that of the straight portion of a commercial 8 Fr double-J stent. The performance of the porous stent improves considerably more (47.5%) than that of the 8 Fr stent (30.6%) upon removal from the tube, illustrating the effectiveness of the radially aligned porosity for drainage. While further studies are required to explore other potential benefits of the porous stent design such as antimicrobial behavior, drug release, and biodegradability, we conclude that the newly-developed porous chitosan ureteral stent has considerable potential as a medical device.